Energy storage using NaOH phase change material for solar thermal application at constant heat flux. Issue 1 (July 2021) - Kumar, B; Das, M K; Roy, J N
Abstract: There is a mismatch between energy demand by consumers and supply from the sun. Therefore, we store Solar Energy in the phase change material (PCM) for storage energy. We used medium temperature range salt, Sodium hydroxide (NaOH), melting temperature at 591 K and heat of fusion 160 kJ/kg. We did the numerical simulation using COMSOL Multiphysics®, we kept radially variable surface flux at the bottom of the container. Linearly variable flux at the centre is 78 kW/m 2 and 18 kW/m 2 at the periphery. For numerical analysis, we used 3D enthalpy based model. We found that the bulk temperature of NaOH reaches about 800 K after 6 hours and total energy stored by the PCM is about 21 MJ. This amount of energy is very useful for domestic and small industrial process.